2016
DOI: 10.1371/journal.pone.0147360
|View full text |Cite
|
Sign up to set email alerts
|

Surface Phosphatidylserine Is Responsible for the Internalization on Microvesicles Derived from Hypoxia-Induced Human Bone Marrow Mesenchymal Stem Cells into Human Endothelial Cells

Abstract: BackgroundPrevious data have proven that microvesicles derived from hypoxia-induced mesenchymal stem cells (MSC-MVs) can be internalized into endothelial cells, enhancing their proliferation and vessel structure formation and promoting in vivo angiogenesis. However, there is a paucity of information about how the MSC-MVs are up-taken by endothelial cells.MethodsMVs were prepared from the supernatants of human bone marrow MSCs that had been exposed to a hypoxic and/or serum-deprivation condition. The incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 53 publications
1
63
0
Order By: Relevance
“…More specifically, TIM4 is a phagocytic receptor that recognizes phosphatidylserine (PS), a phospholipid that is abundant in EVs. Blocking TIM4 in macrophages reduced the uptake of leukemia cell-derived exosomes, which suggests a possible role for PS in exosome internalization [8, 9, 13, 45, 47, 62, 93]. …”
Section: Mechanisms Of Ev-cell Interactions and Uptakementioning
confidence: 99%
“…More specifically, TIM4 is a phagocytic receptor that recognizes phosphatidylserine (PS), a phospholipid that is abundant in EVs. Blocking TIM4 in macrophages reduced the uptake of leukemia cell-derived exosomes, which suggests a possible role for PS in exosome internalization [8, 9, 13, 45, 47, 62, 93]. …”
Section: Mechanisms Of Ev-cell Interactions and Uptakementioning
confidence: 99%
“…Plasma membrane bleb formation is regulated by a host of factors which modulate deformability and bending of the membrane, including the lipid composition and organization of the peripheral cytoskeleton, to alter membrane fluidity and deformability. MVs display unique lipid characteristics, such as the externalization of the phospholipid phosphatidylserine (PS), which has been demonstrated to promote uptake by recipient cells . The phospholipid lysophosphatidylcholines, the sphingolipid sphingomyelins, and acylcarnitines, the fatty acyl esters of L‐carnitine, have also been found to be enriched in MVs .…”
Section: Microvesicle Biogenesismentioning
confidence: 99%
“…MVs display unique lipid characteristics, such as the externalization of the phospholipid phosphatidylserine (PS), 64 which has been demonstrated to promote uptake by recipient cells. 65 The phospholipid lysophosphatidylcholines, the sphingolipid sphingomyelins, and acylcarnitines, the fatty acyl esters of L-carnitine, have also been found to be enriched in MVs. 66 The prominent plasma membrane lipid cholesterol is thought to play an important role in MV formation, as its depletion reduces MV formation.…”
Section: Microvesicle Biogenesismentioning
confidence: 99%
“…This lipid has been identified on the surface of various types of EVs, derived from various types of cells, and has been described as an evolutionary conserved immunosuppressive signal which promotes tolerance and prevents the activation of the immune system (87). Recently, Wei et al have demonstrated that phosphatidylserine on the surface of MSC-derived microvesicles is essential for their uptake by human umbilical vein endothelial cells (HUVECs), however, the role of this lipid in MSC-EV-derived immunosuppression is still unexplored (88). …”
Section: Clinical Application With Mesenchymal Stromal Cells For the mentioning
confidence: 99%